2012
DOI: 10.1088/0957-4484/23/27/275603
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a nickel nanowire mesh electrode suspended on polymer substrate

Abstract: We report on an efficient strategy for the fabrication of an ultra-long suspended nanowire mesh suitable for nanodevice architectures on a polymer surface. First, nickel nanowires are synthesized directly on a template substrate by magnetron sputtering. Laser interference lithography followed by deep reactive ion etching is used to create the nanograted template substrate constituted of one-dimensional line pattern arrays of 240 nm in periodicity. Ordered alignment of ultra-long nanowires (∼180 nm in diameter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The nanowires have a homogenous morphology with a mean diameter of ≈145 nm (corresponding to the width of the grates) and a length up to 1 cm (corresponding to the size of the substrate). The preferential growth of nickel on the top surface of the grating structures can be mainly attributed to the following mechanisms: (i) the low directionality of the deposition process; (ii) the low width of the nanotrench separating two subsequent nanogrates; and (iii) the high depth-to-width ratio of the trenches (here, typically 12) [25,28]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanowires have a homogenous morphology with a mean diameter of ≈145 nm (corresponding to the width of the grates) and a length up to 1 cm (corresponding to the size of the substrate). The preferential growth of nickel on the top surface of the grating structures can be mainly attributed to the following mechanisms: (i) the low directionality of the deposition process; (ii) the low width of the nanotrench separating two subsequent nanogrates; and (iii) the high depth-to-width ratio of the trenches (here, typically 12) [25,28]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we demonstrated the possibility to synthesize an array of aligned Ni nanowires on a patterned silicon surface [25]. In this letter we present a simple and efficient method to prepare an array of highly ordered coaxial nickel/graphene-stacks core–shell nanowires with a length up to 1 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The most hydrophobic polymers (fluoropolymers, silicones) have a contact angle on flat surfaces that is rarely higher than 110°. , The contact angle increases with the roughness of the surface. , Therefore, plenty of work has been devoted to increase the roughness of the surfaces by using lithography, templating techniques, induced phase separation, crystal growth, and etching. However, these techniques are difficult to apply to large and complex surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of multifunctional films with nanomaterials such as transparent conductive film (TCF) [1,2] and molecular sieve separation membrane [3,4] can be expressed in terms of macroscopic properties such as electrical, optical, and mechanical characteristics in the field of materials processing for the fabrication and production. Although proper instruments, e.g.…”
Section: Introductionmentioning
confidence: 99%